IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT, SIKAP DAN PERILAKU POSITIF SISWA DI MA HIDAYATUL MUBTADIIN LAMPUNG SELATAN - Deis Novita Sari; M. Nasor; Etika Pujianti; Suci Hartati (UNISAN JURNAL, 2022)
This research focuses on: (1) How is the implementation of character education about wanting to be happy, behavior, and positive outcomes for students at MA Hidayatul Mubtadiin Jati Agung (2) What about the problem of implementing character education at MA Hidayatul Mubtadiin Jati Agung (3) and what are the supporting factors and constitution of the implementation of this character education. This study uses a qualitative approach with a descriptive method. Therefore, this research is a qualitative descriptive study. Research data were collected through observation, interviews, and documentaries. And for data that looks bright, categorization is made with a coding system. The validity of the data is done through the triangulation method. Data were analyzed during and after the study. The results showed that the implementation of character education in MA Hidayatul Mubtadiin Jati Agung there are main competencies that are mastered by each teacher, namely; RPP regulates competence, curriculum implementation and evaluation.